STRATEGIC FORMULATION FOR FREE TRADE AGREEMENT CASE ON INDONESIAN CAR MANUFACTURE - Rr. Endang Wahyuni; Wiwi Wirda; Haris Fadillah (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The aim of this study is to investigate business strategy employed by a leading car parts manufacturer in Indonesia, which intend to increase export among ASEAN economic community policy. The study focused on subjectivity of business management strategic formulation using SWOT, IE SWOT 4K and QSPM analysis in table, diagram and graphic.  There are five respondents from  each department as the top management who responsible for making  strategy and giving decision for the department. There  are five respondents from each following department: export import, production, business planning, marketing and finance. Results from EFE matrix analysis (total score 2.94) is 2.35 (opportunity) and 0.59 (threat), meaning that PT Denso Indonesia responds the opportunity and threat well because the company’s opportunity could solve the outside threat. Results from IFE matrix analysis (3.15) is 2.69 (strength) and 0.46 (weaknessess), meaning that PT Denso Indonesia has strength more than weaknessess. Results from SWOT 4K analysis is 3.48 (opportunity), 3.28 (threat), 3.87 (strength) and 3.50 (weaknessess). It means that the company’s performance could be determined by combination of internal and external factors because those two factors should be determined  in SWOT analysis. QSPM Matrix shows the score of each strategies .  For the first strategy is 8.31 and the second is 7.21 which means the most important of PT Denso business strategy is for making the product differentiation or knowing as diversification such as an innovation product among others OEM as the competitors or do differentiation from its previous product for competitive advantage by innovating the previous design, quality, price and others.